Registration of 'TN11‐5140' Soybean Cultivar. Issue 2 (4th January 2018) - Smallwood, Chris; Fallen, Ben; Pantalone, Vince
Abstract : The conventional (non‐genetically modified) soybean [ Glycine max (L.) Merr.] cultivar (Reg. No. CV‐525, PI 685014) 'TN11‐5140' was developed by the University of Tennessee Agricultural Experiment Station and released in 2017. TN11‐5140 is derived from an F21 single plant reselection (exceedingly uniform, >99.9% homozygous) from the University of Tennessee cultivar 5601T. It has white flowers, gray pubescence, tan pod wall, a determinate growth habit, and yellow seeds with buff hila. TN11‐5140 and 5601T share many desirable traits, including high yield, broad adaptability, and resistance to stem canker and southern root knot nematode. TN11‐5140 matures 3 to 4 d later than 5601T and has a relative maturity of 6.0, giving it a unique maturity niche for regions of the southern United States. TN11‐5140 produces higher‐than‐average seed oil content and is capable of producing high meal protein (≥47.5%.). Yield performance for TN11‐5140 has been very robust in regional field tests over many years. Given the strong yield, unique maturity niche, ability to produce high meal protein, and resistance to stem canker and southern root knot nematode, TN11‐5140 will be a useful soybean cultivar for producers and processors, as well as for breeders seeking to make further genetic improvements by crossing with elite parents.